The Coxib case: Are EP receptors really guilty?. (June 2016) - Santilli, Francesca; Boccatonda, Andrea; Davì, Giovanni; Cipollone, Francesco
Abstract: The effects of nonsteroidal anti-inflammatory drugs (NSAIDs) originate from the inhibition of cyclooxygenase (COX), which converts arachidonic acid (AA) to prostaglandin H2 (PGH2 ). COX consists of two isoforms, called COX-1 and COX-2. Increasing drug selectivity for COX-2 is associated with higher CV risk. Indeed, Coxibs are shown to favour a prothrombotic state, predisposing patients to myocardial infarction (MI) or thrombotic stroke, and to counter the effects of antihypertensive drugs. Indeed, Coxibs affect kidneys, by dysregulating glomerular filtration and salt/water homeostasis. Eventually, recent data associate Coxibs to "amazing" side effects such as acute hepatitis, hyperkalemia and atrial fibrillation or flutter. The circulating concentrations reached in vivo regulate the selectivity towards one of the two COX isozymes. Thus, both tNSAIDs and Coxibs seem to be able to interfere with COX-2 activity, but the interaction depends on the concentration at which each drug may inhibit PGs synthetase in different tissues. PG synthesis inhibition leads to a multiplicity of effects which can be due to the activation of four E-type prostanoid (EP) receptors, which show differential patterns of tissue distribution. Moreover, nitric oxide (NO) bioavailability and its relation with the endogenous nitric oxide synthase (NOS) inhibitors asymmetric dimethylarginine (ADMA) and l-NG-monomethylarginine (l-NMMA), renin release by juxtaglomerular cells and aldosterone pathway, seem to determine NSAID safety also. These changes may powerfully synergize with NSAID-induced prostaglandin (PG) modifications, thus regulating vascular side effects. Highlights: tNSAIDs and Coxibs can interfere with COX-2 activity, thus inhibiting PGs synthetase. PGE2 effects depend on the activation of four EP receptors (EPR) in different tissues. NSAID effects on platelets differ among the myocardium, vascular wall and kidney. EPR pathways in different tissues may explain the variable NSAID effect on platelets.